2016
DOI: 10.3389/fcimb.2016.00062
|View full text |Cite
|
Sign up to set email alerts
|

Interactions “Candidatus Liberibacter solanacearum”—Bactericera cockerelli: Haplotype Effect on Vector Fitness and Gene Expression Analyses

Abstract: “Candidatus Liberibacter solanacearum” (Lso) has emerged as a serious threat world-wide. Five Lso haplotypes have been identified so far. Haplotypes A and B are present in the Americas and/or New Zealand, where they are vectored to solanaceous plants by the potato psyllid, Bactericera cockerelli (Šulc) (Hemiptera: Triozidae). The fastidious nature of these pathogens has hindered the study of the interactions with their eukaryotic hosts (vector and plant). To understand the strategies used by these pathogens to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 44 publications
1
43
0
1
Order By: Relevance
“…These differences in gene expression between uninfected insects and insects exposed to LsoA-and LsoB-infected plants could be associated with the colonization of the insect AC or they could be in response to modifications of the plant's composition as a result of Lso infection (Wallis et al, 2015). The differences observed between insects exposed to LsoAand LsoB-infected plants may indicate differences in Lso pathogenicity between the haplotypes (Yao et al, 2016). However, neither the DUF1946 nor the von Willebrand factor type D domains were predicted in the protein; therefore, BcVg6-like protein might not be able to bind Lso.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These differences in gene expression between uninfected insects and insects exposed to LsoA-and LsoB-infected plants could be associated with the colonization of the insect AC or they could be in response to modifications of the plant's composition as a result of Lso infection (Wallis et al, 2015). The differences observed between insects exposed to LsoAand LsoB-infected plants may indicate differences in Lso pathogenicity between the haplotypes (Yao et al, 2016). However, neither the DUF1946 nor the von Willebrand factor type D domains were predicted in the protein; therefore, BcVg6-like protein might not be able to bind Lso.…”
Section: Discussionmentioning
confidence: 99%
“…To obtain colonies infected with LsoA and LsoB, respectively, insects from the Lso‐free colonies were transferred to tomato plants previously infected with LsoA or LsoB. Plants and insects were tested using SSR1 primers (Lin et al ., ) to define the Lso haplotype, as previously reported (Yao et al ., ).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…The present study confirms previous findings (Yao et al ., ) that crosses between Lso B‐infected insects produce fewer eggs than crosses between Lso‐free psyllids. This result might support the observed trade‐off between immune defense and reproduction, both energetically demanding processes (Schwenke et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Also, previously, it was shown that the effects of Lso infection in B. cockerelli can differ depending on the Lso haplotype. The infection with each Lso haplotype resulted in the decrease of B. cockerelli fecundity, but only the infection with Lso B reduced the nymphal survival (Yao et al ., ). On potato and silver leaf nightshade, Lso‐infected B. cockerelli nymphs developed faster than uninfected psyllids, but their mortality was higher (Thinakaran et al ., ).…”
Section: Discussionmentioning
confidence: 99%